Family Empowerment Method Modern Dressing Based to Increase Diabtes Mellitus Patients with Diabetic Ulcer - Retno Sumara; Siswanto Agung Wijaya; Diah Priyantini; Aries Chandra Anandita; Sevia Ofarisma N (International Journal of Scientific Multidisciplinary Research, 2023)
Diabetic ulcer is lower extremity illness in diabetic patients with sensory, motoric, autonomic neuropathy, and or limbs blood vessel disorder as the characteristics. Patients with diabetic ulcer often experience psychological stress as the result of the infection of the ulcer itself or the operation procedure, thus negatively affects patients’ self-concept, self-worth, quality of life, physiological and psychological health, hope to recover, and their spirituality. This research aimed to recognize the effect of family empowerment method modern dressing based in inflating diabetic ulcer patients’ quality of life. This research utilized pre-experimental with one group pretest-posttest design. The population and sample in this research are diabetic ulcer patients. The sampling technique used was purposive sampling with the total of 53 respondents. The instrument used was WHOQOL (The World Health Organization of Quality of Life). The research found that patient’s QoL before family empowerment was given, the moderate QoL (Quality of Life) was 41 respondents (77.4%) and the good QoL was 12 respondents (22.6%). After the treatment using the aforementioned method, the good QoL increased to 28 respondents (52.8%), the moderate QoL became 7 respondents (13.2%) and the very good QoL increased as much as 18 respondents (34%). Wilcoxon analysis test resulted ρ 0,000, meaning that there was an effect of family empowerment method modern dressing based to patients with diabetic ulcer